Evaluation of the elastic critical load of tapered columns with circular or square hollow sections - Baptista, A. M. (2010)
This paper presents a method of evaluation of the elastic critical load of tapered members with circular and square cross-sections, under simple compression. The cross-sections of these members may be full solid or hollow, with constant wall thickness, and their external dimensions linearly vary between the column ends. This method is an adaptation of Euler’s equation, by means of the introduction of a coefficient calibrated after the results of a large parametrical study. The results obtained with this method show a very good agreement with those obtained by other analytical and numerical methods. The main advantage of this method lies in the simplicity of its application, allowing a very fast calculation when compared with numerical methods, based on the finite element method for example, or with analytical solutions requiring the solving of complicated mathematical expressions.